Evaluation of the Erosive Potential of Acidic Candies Consumed by Children and Teenagers - Jeison Gabriel da Silva; Maria Mercês Aquino Gouveia Farias; Eliane Garcia da Silveira; Silvana Marchiori de Araújo; Beatriz Helena Eger Schmitt (Journal of Pharmacy and Nutrition Sciences, 2013)
This research aims at investigating the acidity of candies commonly consumed by children and teenagers. Eight flavors of candy produced by the brand Halls Kraft Foods Brazil Ltda.®: cherry, extra strong, watermelon, strawberry, mint, menthol, wild strawberry and chantilly cream strawberry were analyzed. The candies were crushed. Five grams of crushed candy were added to 10 ml of doubly deionized water and stirred until all candy was dissolved. The pH was measured in triplicate using a potentiometer and combined glass electrode (Tec-2 Tecnal). Fifteen grams of crushed candy were added to 30 ml doubly deionized water. The titratable acidity was measured by adding 100 μl of 0.1 M NaOH to the solution under constant stirring until a pH of 5.5 was reached. This procedure was performed for each of the flavors. Mineral water was used as a negative control and citric acid as positive control. The results were statistically analyzed by the Variance Analysis (ANOVA). Comparisons of means were performed by the Scott Knott Test, at a 5% level of significance (p <0.05). The results showed that all candies had pH values below 5.5, ranging from 3.6 to 5.2. These values were significantly different from the positive and negative controls. The flavors Chantilly Cream Strawberry and Wild Strawberry have shown to be the candies with highest erosive potential due to their lower pH values and higher intrinsic buffer capacity. It is concluded that the candies have erosive potential and their frequent use can contribute to the development of dental erosion.